Respostas

2014-09-02T22:42:14-03:00
(3x-1)+2(3-x)=86x-2+6-2x=86x-2x=8+2-64x=4x=4/4x=1 2(3x-1)+2(3x+1)=86x-2+6x+2=86x+6x=8-2+212x=8x=8/12x=2/3 (voce pode simplificar por 4 a fração)  7(x-1)=2(3x+1)7x-7=6x+27x-6x=7+2x=9 1+4(x-5)=01+4x-20=04x=20-14x=19x=19/4 4(x-2)+3(2x-1)=6(2x-3)4x-8+6x-3=12x-184x+6x-12x=8-18+3-2x=-7 (-1) (multiplica por menos para mudar o sinal)2x=7x=7/2 x-(x-1)=12-(3x-2)x²-x=36+24x=60
2014-09-02T22:51:20-03:00
1 +7x -3 (1 -2x) = 2 (3 -4x) -8 (x +9)
1 +7x -3 +6x = 6 -8x -8x -72
7x +6x +8x +8x = 6 -72 -1 +3
29x = -64
x= -64/29